La pedagogia del paesaggio. La poesia-stlanik di Fabio Pusterla - Baldacci , Alessandro (Toruńskie Studia Polsko-Włoskie, 2022)
This article explores the interest of Fabio Pusterla's poetry for the representation of the landscape, as well as the constant ecological attention that is revealed within his texts. In particular, it is shown how the representation of nature presents anti-idyllic characteristics and, at the same time, embodies a pedagogical value and resistance that assimilates nature to the profound reasons of poetry. The essay focuses on the symbolic and "political" value that Pusterla entrusts to trees and plants as witnesses of a moral and civil tension that feeds the privileged dialogue between ecology and lyric in contemporaneity.